Caracterización Hidrológica y Modelo Hidráulico de la cuenca del río Casacay. - Espinoza, J.; Salazar, W.; Pérez, S.; Guamán, E. (My University, 2020)
This research has as main objective the determination of a mathematical model that allows the calculation of flow rates with the entry of the height of the water level of certain determined points and compare it with the limnimetric readings where it will be verified that the results are similar, with the Logarithmic regression aid. The importance of the GIS software (Geographic Information Systems) is evident, which helps the physical-spatial and hydraulic analysis, serving for the planning and characterization of water basins. The problem that led to the study of the Casacay river basin, is the lack of adequate means to graphically represent the nearby basins, or perform calculations or estimates in the management of the water resource, there is also a lack of statistical information that help to perform Studies based on historical data, to measure the different evolutions of the basin with respect to exploitation times, also perform histograms to simulate numerical behavior, predict load losses or flooding in neighboring areas. One of the systems used for direct capacity, is the capacity with windlass which was used for the preparation of this study, together with SENAGUA, which is the regulator of water resources in the country, helped with relevant information for this have the necessary inputs to represent the representative equation and predict flow rates during which period of the year.
Esta investigación se tiene como objetivo principal la determinación de un modelo matemático que permita el cálculo de caudales con el ingreso de la altura del nivel de agua de ciertos puntos determinados y compararlo con las lecturas limnímetricas donde se verificará que los resultados se asemejan, con la ayuda de regresión logarítmica.Se evidencia la importancia del software SIG (Sistemas de información geográfica), que ayudan al análisis físico-espacial e hidráulicas, sirviendo para la planeación y caracterización de cuencas hídricas.El problema que motivo al estudio de la cuenca del río Casacay, es la falta de medios adecuados para representar gráficamente las cuencas cercanas, ni efectuar cálculos o estimaciones en la gestión del recurso hídrico, también se evidencia la falta de información estadística que ayuden a realizar estudios basados en datos históricos, para medir las diversas evoluciones de la cuenca con respecto a tiempos de explotación, así mismo realizar histogramas para simular comportamiento de forma numérica, predecir perdidas de carga o inundaciones en zonas vecinas. Uno de los sistemas que se emplean para el aforo directo, es el aforo con molinete el cual fue empleado para la elaboración de este estudio, junto SENAGUA, el cual es el ente regulador de los recursos hídricos del país, ayudo con información relevante para así tener los insumos necesarios para representar la ecuación representativa y predecir caudales durante cual periodo del año.
Keywords: SIG; CASACAY; REGRESIÓN LOGARÍTMICA; RECURSO HÍDRICO